Social Capital Of Galian Owners In Maintaining Galian C In Mawar Hamlet, Kumbang Village, Pelangi District, Pasuruan Regency - Ika Nursyafitri (Jurnal Ilmu Sosial Mamangan, 2020)
Mining in Mawar Hamlet, Kumbang Village, Pelangi District, Pasuruan Regency is a type of illegal mining, but mining activities have been carried out since 1984 until now. So this research aims to analyze the social capital of the owner of the excavation in maintaining the C quarry in the Rose Village with the established network. The method used is a qualitative research method to explore more complete data, and uses a case study approach because an incident in 2015 was marked with the issue of illegal mining permits that were evicted by the Civil Service Unit (Satpol PP of Pasuruan Regency). This study uses the theory proposed by Pierre Bourdie about social capital. Social capital can be related to economic capital, cultural capital, and symbolic capital. Thus, the emergence of the capital generated by the owner of the excavation originated from the habitus as a daily habit carried out by the agent, the network relationships formed were also strategies to strengthen the agent's position. Keywords: Social Capital, Galian C Mining, Illegal Mining